Inflation risk premia in the term structure of interest rates - Peter Hördahl; Oreste Tristani (European Central Bank (ECB), 2007)
This paper estimates the size and dynamics of inflation risk premia in the euro area, based on a joint model of macroeconomic and term structure dynamics. Information from both nominal and index-linked yields is used in the empirical analysis. Our results indicate that term premia in the euro area yield curve reflect pre-dominantly real risks, i.e. risks which affect the returns on both nominal and index-linked bonds. On average, inflation risk premia were negligible during the EMU period but, occasionally, subject to statistically significant fluctuations in 2004-2006. Movements in the raw break-even rate appear to have mostly reflected such variations in inflation risk premia, while long-term inflation expectations have remained remarkably anchored from 1999 to date.
Keywords: E43; E44; 330; central bank credibility; ination risk premia; Term structure of interest rates; Inflationsrate; Risikoprämie; Zinsstruktur; Geldpolitik; Schätzung; EU-Staaten